The Influence of Industrial Civilization to Ecological Civilization on the Concept and Behavior of Sports - Zhang, Yi; Liang, Huawei (Journal of Theory and Practice of Management Science, 2023)
The formation of sports concepts is influenced by various factors, such as institutional policies, level of economic development, education level, etc., lifestyle, etc. the form of human civilization is also an important influencing factor. the development of human society may be divided into primitive civilization, agrarian civilization, industrial civilization and ecological civilization. This paper tries to analyze the changes and evolution of sports concepts and the influence on sports behavior from industrial civilization to ecological civilization. The first-level index gives weight to 0.5, reflecting the equality between teachers and students. After that, the entropy weight method is used to determine the weight of each second-level index, which is an objective weighting method. The less the variation degree of the index is, the less the information it reflects, and the lower the corresponding weight should be.